Pendekatan Integratif Toksikologi Industri, Higiene Industri, Dan K3 Dalam Mewujudkan Lingkungan Kerja Yang Aman Dan Sehat - Abid Farhan; Afzidan Lutfi Amaryu Marpaung; Iswar Saputra Nasution; Abdurrozzaq Hasibuan (Annusfy : Journal of Multidisciplinary Research, 2026)
The purpose of this study was to determine the increasing potential for occupational safety and health risks due to exposure to chemicals, physical factors, and unsafe working conditions. A partial approach to risk control is considered ineffective in addressing this complexity. This study aims to analyze the role and integration of industrial toxicology, industrial hygiene, and occupational safety and health (OHS) in creating a safe and healthy work environment. The method used was a literature study by reviewing various scientific sources in the form of journals, books, and reports from relevant international institutions. The results of the study indicate that industrial toxicology plays a role in understanding the impact of hazardous materials on health, industrial hygiene in identifying and controlling exposure, and OHS in managing risks systematically through a managerial approach. The integration of these three fields has been proven to provide a more comprehensive approach to occupational risk control.